GASTROPODA (MOLLUSCA) ASSOCIADOS A Caulerpa racemosa (FORSKAL) LAMOUROUX, 1809 NA PRAIA DO CUPE, IPOJUCA, PERNAMBUCO, BRASIL - Oliveira, Ana Paula Andrade de; Pinto, Stefane de Lyra; Alves, Marcos Souto; Leite, Maria Fernanda Silva; Almeida, Sérgio Mendonça de; Barros, Carolina Notaro de (Revista Nordestina de Zoologia, 2012)
This research aimed to know a mollusk Gastropoda biodiversity associated with the macroalgae Caulerpa racemosa (Forskal) Lamouroux in Cupe beach, Pernambuco, Brazil. The samples of the algae were collected monthly in diurnal low tides during the period of January to December of 2005. The material was fixed in formalin saline 4% neutralized with borax, subsequently used the sorting, identifying the rate of Gastropoda and measuring the volume of samples. They were calculated density, abundance and frequency of species. Prosobranchia was the most representative subclass dominating on the other subclasses. The total density varied over the period was higher between the months of the dry period. Ware examined 7.105 individuals, totaling 28 species. Nine species had 100% of frequency being considered constant. The species Caecum ryssotitum that presented the highest density among Prosobranchia, with average density of 86,95 ind.100 ml-1, a minimum of 14,79 ind.100 ml-1 in may 2005 and a maximum of 206,45 ind.100 ml-1 in november 2005.